Research trends and hotspots of ketamine from 2014 to 2023: a bibliometric analysis - Wang, Yida; Chang, Sile; Chen, Dongxu (Frontiers in Neuroscience, 2024)
Background: Despite this growing interest, there remains a lack of comprehensive and systematic bibliometric analyses of ketamine research. This study aimed to summarize the progress in ketamine research through bibliometric analysis, providing insights into the development and direction of the field. Methods: Publications related to ketamine were retrieved from the Web of Science Core Collection (WoSCC) database on February 15, 2024. In conducting a comprehensive bibliometric analysis, a variety of bibliographic elements were meticulously collected to map the landscape of research within a specific field. Results: Between January 1, 2014, and December 31, 2023, a total of 10,328 articles on ketamine research were published across 1,752 academic journals by 45,891 authors from 8,914 institutions in 128 countries. The publication volume has shown a steady increase over this period. The United States of America (USA) and the People's Republic of China lead in both publication and citation counts. The National Institute of Mental Health (NIMH) and Yale University emerge as the most active institutions in this research domain. Carlos Zarate of the NIH National Institute of Mental Health was noted for the highest number of significant publications and received the most cocitations. The analysis revealed key research themes including mechanism of action, adverse events, psychiatric applications, and perioperative implications.This study provided comprehensive bibliometric and knowledge mapping analysis of the global ketamine research landscape, offering valuable insights into the trends, key contributors, and thematic focus areas within the field. By delineating the evolution of ketamine research, this study aims to guide future scholarly endeavors and enhance our understanding of ketamine's therapeutic potential.